Firm-specific production factors in a DSGE model with Taylor price setting - Gregory De Walque; Frank Smets; Raf Wouters (National Bank of Belgium, 2006)
This paper compares the Calvo model with a Taylor contracting model in the context of the Smets-Wouters (2003) Dynamic Stochastic General Equilibrium (DSGE) model. In the Taylor price setting model, we introduce firm-specific production factors and discuss how this assumption can help to reduce the estimated nominal price stickiness. Furthermore, we show that a Taylor contracting model with firm-specific capital and sticky wage and with a relatively short price contract length of four quarters is able to outperform, in terms of empirical fit, the standard Calvo model with homogeneous production factors and high nominal price stickiness. In order to obtain this result, we need very large real rigidities either in the form of a huge (constant) elasticity of substitution between goods or in the form of an elasticity of substitution that is endogenous and very sensitive to the relative price.
Keywords: E1; E3; 330; Inflation persistence; DSGE models; Dynamisches Gleichgewicht; Preisrigidität; Lohnrigidität; Neoklassische Synthese; New-Keynesian Phillips Curve